Synthesis, characterization, and determination of sono-photochemical properties of Si(IV) Phthalocyanine containing axial 7-hydroxy-5-methyl-[1,2,4]triazolo[1,5-a]pyrimidine groups - Buyuk, Esma; Penlik, Yunus; Kekec, Gunseli Guney; Gorduk, Semih (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Cancer, which is caused by the uncontrolled growth and proliferation of cells in different tissues and organs in the body, is one of the deadliest diseases. As an alternative to conventional cancer treatment methods with various disadvantages, minimally invasive methods have been developed. One of these methods, PDT, aims to create cellular damage using light-sensitive agents, while SDT creates a similar effect using ultrasound energy. SPDT combines ultrasound energy and a light source and offers a higher therapeutic effect in superficial and deep-seated tumours by reducing the dose of sensitizers. In this direction, phthalocyanine compounds used as sensitizers are frequently encountered. In this study, axial 7-hydroxy-5-methyl-[1,2,4]triazolo[1,5-a]pyrimidine di-substituted Silicon(IV) phthalocyanine (SiPc-MTP) was synthesized, and characterization studies were carried out by UV-Vis, FT-IR, MALDI-TOF MS, and H-1 NMR methods. The suitability for PDT and SPDT applications was determined using photophysical, photochemical, sonochemical, and sonophotochemical methods in dimethylformamide (DMF) and dimethylsulphoxide (DMSO) solvents. In photochemical studies, the singlet oxygen yield of SiPc-MTP was determined as 0.59 in DMF and 0.63 in DMSO. As a result of sono-photochemical studies, these values were obtained as 0.80 in DMF and 0.84 in DMSO. When the results were compared, it was determined that the values belonging to the SPDT method were a sensitizer agent with a significantly higher singlet oxygen yield.
Keywords: 7-hydroxy-5-methyl-[1,2,4]triazolo[1,5-a] pyrimidine; Silicon(IV) Phthalocyanine; Photochemical; SPDT; PDT; BIOLOGICAL EVALUATION; PHOTODYNAMIC THERAPY; IN-VITRO; CANCER; BEARING; Chemistry; Crystallography